Treatment of cardiotoxicity in patients with invasive breast cancer during neoadjuvant chemotherapy - Grigorii A. Ignatenko; Igor E. Sedakov; Olga V. Kolycheva; Oleg I. Kaganov; Andrei E. Orlov; Nadezhda N. Bondarenko (Наука и инновации в медицине)
Aim – assessment of the effectiveness of complex therapy to reduce the development of early cardiovascular complications.